Previously identified patellar tendinopathy risk factors differ between elite and sub-elite volleyball players - Janssen, I.; Steele, J. R.; Munro, B. J.; Brown, N. A. T. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Patellar tendinopathy is the most common knee injury incurred in volleyball, with its prevalence in elite athletes more than three times that of their sub-elite counterparts. The purpose of this study was to determine whether patellar tendinopathy risk factors differed between elite and sub-elite male volleyball players. Nine elite and nine sub-elite male volleyball players performed a lateral stop-jump block movement. Maximum vertical jump, training history, muscle extensibility and strength, three-dimensional landing kinematics (250 Hz), along with lower limb neuromuscular activation patterns (1500 Hz), and patellar tendon loading were collected during each trial. Multivariate analyses of variance (P < 0.05) assessed for between-group differences in risk factors or patellar tendon loading. Significant interaction effects were further evaluated using post-hoc univariate analysis of variance tests. Landing kinematics, neuromuscular activation patterns, patellar tendon loading, and most of the previously identified risk factors did not differ between the elite and sub-elite players. However, elite players participated in a higher training volume and had less quadriceps extensibility than sub-elite players. Therefore, high training volume is likely the primary contributor to the injury discrepancy between elite and sub-elite volleyball players. Interventions designed to reduce landing frequency and improve quadriceps extensibility are recommended to reduce patellar tendinopathy prevalence in volleyball players.